2008
DOI: 10.1021/la703732h
|View full text |Cite
|
Sign up to set email alerts
|

Penetration and Growth of DPPC/DHPC Bicelles Inside the Stratum Corneum of the Skin

Abstract: The effect of dipalmitoyl phosphatidylcholine (DPPC)/dihexanoyl phosphatidylcholine (DHPC) bicelles on the microstructure of pig stratum corneum (SC) in vitro was evaluated. The physicochemical characterization of these nanoaggregates revealed small disks with diameters around 15 nm and a thickness of 5.4 nm. Upon dilution, the bicelles grow and transform into vesicles. Cryogenic scanning electron microscopy (cryo-SEM) images of the SC pieces treated with this system showed vesicles of about 200 nm and lamella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 44 publications
4
64
0
1
Order By: Relevance
“…However, it is necessary to consider that the DPPC/DHPC bicelles increase in size, forming large bilayers by a dilution effect. This behavior is similar to that reported in surfactant-lipid micellar systems [17,18] and has been recently reported for DPPC/DHPC bicellar systems [19]. Then, we can assume that small DPPC/DHPC discoidal bicelles are able to pass through the SC layers and by mixing with SC lipids and influenced by SC hydration, large structures are formed.…”
Section: Effect Of Dmpc/dhpc and Dppc/dhpc Bicelles On The Sc Microstsupporting
confidence: 70%
“…However, it is necessary to consider that the DPPC/DHPC bicelles increase in size, forming large bilayers by a dilution effect. This behavior is similar to that reported in surfactant-lipid micellar systems [17,18] and has been recently reported for DPPC/DHPC bicellar systems [19]. Then, we can assume that small DPPC/DHPC discoidal bicelles are able to pass through the SC layers and by mixing with SC lipids and influenced by SC hydration, large structures are formed.…”
Section: Effect Of Dmpc/dhpc and Dppc/dhpc Bicelles On The Sc Microstsupporting
confidence: 70%
“…[32,55]. Applying the form factor squared of the simplified Gaussian model to SAXS a bilayer thickness value (d B = 5.4 nm) was obtained [32,55]. The size distribution curve obtained by DLS shows a HD value of 11.3 nm and a PI of 0.072.…”
Section: Dppc/dhpc Bicellar Systemsmentioning
confidence: 99%
“…In fact, the interaction of these systems with SC has been reported and although tracking the presence of the bicellar disks in the tissue was not possible, interestingly, vesicles and lamellar-like structures were observed in the lipid intercellular areas of the tissue after treatment with bicellar systems. These structures were probably the result of a structural rearrangement of bicelles inside the cutaneous SC [55]. …”
Section: Dppc/dhpc Bicellar Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, bicellar systems have become a useful membrane mimetic since it provides an oriented media for the study of molecules with biological interest, using solid [6][7][8][9] and solution NMR 10,11 . Bicellar systems are formed from mixtures of the dihexanoylphosphatidylcholine (DHPC) and dimiristoylphosphatidylcholine (DMPC) 4,12 and occasionally, dipalmitoylphatidylcholine (DPPC) [13][14][15] . On the other hand, it has been reported that adding a third lipid, with propensity to form a non-lamellar phase, to the DPPC/SM mixture, increases the permeation of cytolitic proteins 16 .…”
Section: Introductionmentioning
confidence: 99%